2009
DOI: 10.1007/978-3-642-04271-3_80
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Tissue Optical Attenuation to Identify Cancer Using Optical Coherence Tomography

Abstract: Abstract.The lymphatic system is a common route for the spread of cancer and the identification of lymph node metastases is a key task during cancer surgery. This paper demonstrates the use of optical coherence tomography to construct parametric images of lymph nodes. It describes a method to automatically estimate the optical attenuation coefficient of tissue. By mapping the optical attenuation coefficient at each location in the scan, it is possible to construct a parametric image indicating variations in ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 12 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…Similar studies on lesions in the ureter [ 30 ], kidney [ 4 , 33 ], vulva [ 5 ], oral tissue [ 6 ] and lymph node metastasis [ 7 ] confi rmed the ability of OCT to distinguish tissue types based on μ oct . However, an initial study by Cauberg et al on ex vivo human bladder urothelial biopsies showed that factors typical for ex vivo settings (e.g.…”
Section: Attenuation Coeffi Cientsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar studies on lesions in the ureter [ 30 ], kidney [ 4 , 33 ], vulva [ 5 ], oral tissue [ 6 ] and lymph node metastasis [ 7 ] confi rmed the ability of OCT to distinguish tissue types based on μ oct . However, an initial study by Cauberg et al on ex vivo human bladder urothelial biopsies showed that factors typical for ex vivo settings (e.g.…”
Section: Attenuation Coeffi Cientsupporting
confidence: 53%
“…These differences can be elucidated from the light scattering properties [ 2 ] that are measured from the signal decrease with depth from OCT images, [ 3 ] showed differences in scattering properties between normal and cancerous urothelium. Similar studies on lesions in the kidney [ 4 ], vulva [ 5 ], oral tissue [ 6 ] and lymph node metastasis [ 7 ] confi rmed the ability of OCT to distinguish tissue types based on μ oct . However, initial studies on ex vivo human bladder urothelial biopsies showed that factors typical for ex vivo settings (e.g.…”
Section: Functional Octmentioning
confidence: 63%
“…The absolute intensity values in an OCT data set are a function of both tissue type and imaging parameters such as tissue depth, power and incident angle of the light source, imaging optics, and the effects of overlying tissue. Parametric image processing techniques for OCT (14) have been proposed to remove these imaging variations and to provide absolute quantification of the distinction between healthy and malignant tissue. In addition, OCT imaging is performed on fresh tissue, whereas subsequent histologic analysis requires fixation and further processing.…”
Section: Discussionmentioning
confidence: 99%
“…26 During carcinogenesis, a cell is subjected to cellular changes which alter the light scattering properties. Quantification of OCT images using μ oct measured from lesions in the ureter, 12 kidney, 11 vulva, 18 oral tissue, 27 and lymph node metastases 28 confirmed the ability of OCT to distinguish between tissue types based on μ oct . We hypothesize that the attenuation coefficient also correlates with cellular properties of prostate tissue.…”
mentioning
confidence: 59%